Defining and classification of the soft projects as a base for their scope planning - Фаиз Ахмад, Аль Атум Мохаммад (Technology audit and production reserves, 2015)
In this paper we investigate a new class of soft projects, the main feature of which is a significant presence of personality in the design product and its defining role in the use of this product. Today, basic knowledge of soft projects is not enough to effectively manage, although the number of such projects is constantly increasing. The aim of research is to extend the existing knowledge about the nature of the soft projects and further their use as a basis for identifying features of planning their content. To achieve this aim we used methods of analysis, synthesis, graphical modeling. According to the results, the conditions for a successful consumption of product of soft project formed at the time of its creation by changing (formation, development) the necessary worldview competencies of future consumer. On this basis it is formulated the definition of soft project. By means of the proposed model it is shown that a key feature of the classification of such projects depends on two parameters simultaneously - the degree of novelty of variable competence and presence of personality in the product of design. It is shown that the category "competence" for soft projects is considered as a management. Its application for planning the content of soft project involves determining the set of work packages, as well as their rational interconnectedness and duration. In this regard, further development is existed for the traditional model of presentation of hierarchy structure of the project works. The features of its use for educational projects with high degree of softness are considered. It is formulated a hypothesis about the dependence of the duration of work packages, rational correlation types of work, as well as rational forms of realization of the types of works from the heterogeneity of the importance of generated competencies for multiple users. The proposed model, findings and the postulates allow use the traditional tools of content planning for particular class of soft projects. However, this requires additional experimental verification and refinement.